Feedback mode preference and performance improvement with a handheld scanning device. (19th February 2020) - Beckham, Elizabeth Copeland; Burch, Reuben F.; Strawderman, Lesley; Babski-Reeves, Kari; Bian, Linkan; King, Katherine
This study was conducted to determine if combining feedback modes is beneficial for operator performance on a handheld scanning device within the services distribution industry. An industrial handheld scanner was used to examine four feedback conditions: 1) auditory; 2) auditory-visual; 3) auditory-tactile; 4) auditory-visual-tactile. Participants completed one trial under each experimental feedback condition during one experimental session. In each trial, participants scanned 50 boxes during a simulated box scanning task. Task completion time, completion time ranks, hit rate and false alarms were recorded and analysed. While the auditory-visual-tactile feedback combination produced the fastest task completion time, there was no significant improvement in operator performance between the four feedback settings tested. Through further understanding of the most preferred feedback modes, or combination of such, identification of improved scanner settings for this device and task can be made.